Design Thinking Perspective in Entrepreneurship Education - Mufaro Dzingirai (IGI Global, 2023)
To stimulate the exploitation of entrepreneurial opportunities in a circular economy, there is a growing need for educators, especially in the context of universities, to make a paradigm shift from conventional entrepreneurship teaching methodologies to design thinking. As such, the call for a design-based entrepreneurship curriculum has attracted the interests of scholars, researchers, educators, and policymakers in recent years. Unfortunately, little is known about how design thinking processes and tools are being incorporated into entrepreneurship education. Consequently, this chapter captures in detail the worldwide practices and controversies mainly associated with entrepreneurship education from a design thinking standpoint, reviews entrepreneurship education in relation to entrepreneurship development in a circular economy, captures perceptions of academics about design-based entrepreneurship education, proposes recommendations to policymakers and practitioners, and identifies research gaps for further studies.